EVOLUSI SISTEM PENDIDIKAN PESANTREN: TELAAH HISTORIS DAN TANTANGAN KONTEMPORER - Shalahuddin, M.; Basri, Hasan; Suhartini, Andewi (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
Pesantren is the oldest Islamic educational institution in Indonesia, which has undergone various transformations throughout history. This study aims to examine the evolution of pesantren’s educational system from a historical perspective and analyze contemporary challenges faced in the era of globalization and the industrial revolution 4.0. Using a qualitative descriptive approach, data were obtained through case studies and literature reviews. The findings indicate that pesantren's educational system evolved from a traditional model focusing on kitab kuning teachings with sorogan and bandongan methods into a modern pesantren that incorporates general curriculum and digital technology. The main challenges faced by pesantren include technological integration, curriculum modernization, and strengthening its role in religious moderation to counter radicalism. Adaptation strategies implemented by pesantren include digitizing learning processes, developing santripreneurship programs, and integrating character education based on Islamic values. The study concludes that pesantren demonstrates remarkable flexibility in navigating changes without losing its traditional identity. Support from various stakeholders is essential to ensure the sustainability of pesantren’s transformation, allowing it to remain relevant and competitive in the future. Keywords: Pesantren, Educational Evolution, Globalization, Technology, Religious Moderation